Influence of African Swine Fever (ASF) Outbreak on the Socio-Economic Status of Backyard raisers in Aurora - Bumatay, Valin D. (Aurora ASCOT, 2023)
This study investigates the influences of African Swine Fever (ASF) on backyard raisers in Aurora province, providing valuable insights for future policy making. Using a descriptive research design, the study assesses ASF's influence on raisers socio-economic, characteristics, losses, and coping strategies. Conducted in Central Aurora, it involves 55 backyard raisers during the 2019 ASF outbreak, ensuring demographic diversity through total enumeration. The research instrument, an interview guide, covers personal profiles, ASF-related losses, coping strategies, and pre/post-ASF swine raising experiences. Data collection prioritizes informed consent and linguistic clarity, with organization for analysis. Most backyard swine raisers are male, college graduates, residing in medium-sized households, with farming as their primary occupation and primary income source. These raisers, categorized as marginal farmers, predominantly utilized saving as their main source of capital to raise growers or fatteners. The ASF outbreak led to significant decreases in input expenditures, while labor costs for technician incentives decreased, and spending on cleaning and disinfection declined. Some raisers resorted to loans with minimal interest, settling them after compensation receipt, while others arranged payments upon stock sales. During the ASF outbreak, caretakers previously employed by some raisers, were no longer sustained, resulting in a drastic decline in sales. Key interventions recommended include raising awareness of ASF signs, promoting preventive measures facilitating credit access, and enhancing market linkages to improve financial resilience. Ensuring transparent government support, early detection systems, community cooperation and research for ASF prevention are crucial for mitigating losses and building trust. In overall, the study contributes essential insights for targeted strategies to enhance the well-being of backyard raisers in Aurora province, emphasizing the need for sustainable disease management practices. Additionally investing in research and development for ASF prevention strategies is advised for long-term sustainability in the absence of vaccines
Bachelor of Science in Agriculture (Animal Science)